Histopathological Features and Composition of Gut Microbiota in Rhesus Monkey of Alcoholic Liver Disease - Wang, Hong; Yan, Yaping; Yi, Xiaoyan; Duan, Yanchao; Wang, Junfeng; Li, Shanshan; Luo, Lilin; Huang, Tianzhuang; Inglis, Briauna; Li, Xi; Ji, Weizhi; Tan, Tao; et al. (Frontiers in Microbiology, 2019)
Alcohol-induced chronic liver disease (ALD) is becoming the most common liver disease in the world. However, there are no effective, universally accepted therapies for ALD. The etiology of ALD remains blurry so far. Historical evidence has demonstrated a link between the liver and gut microbiota. But it is difficult to distinguish the effect of gut microbiota changes caused by alcohol consumption in humans since the microbiota change detected in humans is complicated by diet and environmental factors. Due to the genetic, physiological, metabolic, and behavioral similarities to humans, the rhesus monkey provides excellent translational validity in preclinical studies, and the diet and environmental conditions can be controlled well in rhesus monkey. In our study, we explored the relationship between ALD and the gut microbiome in the rhesus monkeys with alcoholic liver steatosis. Our results showed that there was a change of the bacterial community structure in monkeys with ALD. Differences of the relative abundances of gut microbiota at phylum, order, family, genus, and species levels were observed between control monkeys and monkeys with ALD, and different pathways enriched in the monkeys with ALD were identified by metagenomic function analysis. Firmicutes, Proteobacteria, Verrucomicrobia tended to increase whereas Bacteroidetes and Actinobacteria decreased in the fecal microbiota of ALD group compared to the control group. Lactobacillales and Lactobacillus significantly decreased in ALD monkeys compared with normal monkeys, Streptococcus was lower in the ALD group compared with the control group. The non-human primate model of ALD will be useful for exploration of the microbiome markers as diagnosis and potentially prognosis for ALD. The ALD model will benefit the development of new therapeutic procedures for treating ALD and provide safety and efficacy evaluation for clinical application.